PEMIDANAAN PENGGUNA NARKOTIKA GOLONGAN I BAGI DIRINYA SENDIRI (STUDI PUTUSAN NOMOR 175/PID.SUS/2021/PN.PTI): Punishment Of Class I Narcotics Users For Themselves (Study Decision Number 175/Pid.Sus/2021/Pn.PTI - Mukhlis, Ryan Arbi Putra; Iskandar, Anang (Faculty of Law, Universitas Trisakti, 2024)
- Abuse and illicit trafficking of narcotics in correctional institutions has increased significantly. In 2021 there were 148 cases of narcotics smuggling into correctional institutions. The distribution of narcotics in prisons is known as a correctional institution-based distribution pattern and involves prisoners who are still undergoing the punishment process for narcotics. The main problem in this article is whether judge's decision no. 175/Pid.Sus/2022/PN Pti which imposes prison sentences on perpetrators of criminal acts of abusing narcotics is appropriate based on Law no. 35 of 2009 concerning Narcotics, (2) what were the judge's considerations in decision No. 175/Pid.Sus/2022/PN Pti did not impose a sentence to undergo rehabilitation. The research method used is a normative-descriptive research method, which is collected using secondary data, then analyzed qualitatively, and conclusions drawn deductively. The conclusion of this research is that prison sentences for class I narcotics abusers are inappropriate based on Law no. 35 of 2009 concerning Narcotics (Study Decision Number 175/Pid.Sus/2021/Pn. Pti), and that the Decision of the Panel of Judges Number 175/Pid.Sus/2021/Pn.Pti which imposed a prison sentence of 10 (ten) months has not been precisely with the aim of punishing narcotics abusers